Investigation on the dynamic thermal storage/release of the integrated PCM solar wall embedded with an evaporator. (November 2022) - Li, Ao; Duan, Shuangping; Han, Rubing; Wang, Chaoyu
Abstract: The integrated phase change materials (PCM) solar wall can store solar energy effectively, which has a broad application prospect. However, the integrated PCM solar wall cannot completely release heat at night. In this paper, the evaporator of the heat pump system is embedded in the integrated PCM solar wall, which can realize the combination of active and passive utilization of solar energy. A numerical study on the thermal storage/release characteristics of the integrated PCM solar wall with an embedded evaporator was carried out in this paper considering its two-dimensional heat transfer. The effect of the thermal release mode, the thermophysical parameters of PCM and the solar radiation intensity on the thermal storage/release characteristics was studied. The simulation results showed that the active thermal release mode increased the released heat by 33.33 kJ/kg, and the proportion of the released heat to the stored heat increases by 30.12%, compared with the passive thermal release mode. Moreover, the increase of the phase transition temperature and the thermal conductivity of PCM can increase the stored heat and released heat, and the latent heat of PCM will increase the stored heat and decrease the released heat. The conclusion can provide a theoretical basis for the research of active and passive solar systems.